Is emergent cervical radiological evaluation mandatory in isolated cranial gunshot injury? (Annals of Medical Research, 2021)
None
Keywords: Cranial Gunshot Injury; Cervical Injury; High-Velocity; Penetrating; Perforating; Tangential.